Financial Performance Mapping of Property Companies After Ibu Kota Nusantara Discourse - I Gusti Ngurah Agung Arya Bhakta Narayana; Teofilus Karnalim; Talitha Sabil Nasywa Arifiansyah; Johana Tania Arviana; Kevin Gasy Sutanto (Penerbit Goodwood, 2026)
Purpose: The development of the IKN will cause a flow of residents from Jakarta to the IKN area. This move will increase the community's need for housing around the IKN. This increase in housing demand affects the performance of property companies, especially those listed on the IDX. Of the 90 property companies on the IDX, it is unclear which companies gave positive and negative responses. This study aims to map the responses of property companies regarding IKN development. Methodology/approach: Data will be extracted from the financial report to carry out financial ratio analysis. After calculating the financial ratios of property companies, researchers divide the results into two categories: “GOOD” and “BAD.” The mapped results were then described using Radar Analysis. All methods were performed in Excel. Results/findings: All eight radar charts show that most companies tend to have